Darwin’s legacy: evolutionary interactions - Smocovitis, Vassiliki Betty (Henry Stewart Talks, 2020)
Ecology and evolutionary interactions, The history of ecology, structure of ecological science, Darwin as an ecologist and as a naturalist, Linnaeus, Humboldt, White, Malthus, Lyell, Wallace, Struggle for existence, Adaptive radiation, Modern ecology and evolutionary biology, Conservation ecology, pollination ecology, plant ecology, invasion ecology